Handbook of research on applications of AI, digital twin, and internet of things for sustainable development - Mishra, Brojo Kishore 1979- (Advances in computational intelligence and robotics (ACIR), 2023)
The increasing interest in Artificial Intelligence (AI), Digital Twin (DT) and Internet of Things (IoT) is progressively playing a wider impact on many different sectors, and and this book offers several applications and challenges in various vital roles such as Product design and lifecycle, Smart Cities, Agriculture, Environment automation, Healthcare, Farming, Wearable, Climate, Sensors, Transportation, Electrical generation, E-governance renewable energy, and eco-system for sustainable growth